The Emerging Social Work techniques in Youth Empowerment programs: A case Study of Youth Empowerment Organizations in Nairobi County - Jeremiah Otieno, Edwine; Osiru Okatta, Timothy; Muhingi Ndege, Wilkins; Mutavi, Teresia; Tedd Okuku, Michael; Okoth Odero, Dr. Vitalis; Mwendwa, David Kimaili (International Journal of Scientific Research and Management (IJSRM), 2018)
Traditional techniques used in social work have become obsolete and ineffective in meeting the contemporary needs of the dynamic population. This has led to the development of new social work techniques that seek to achieve social transformation among the youth. These innovations which are being implemented by youth empowerment organizations are important not only to the social workers that utilize them and their clients but also for the upcoming professionals and institutions that provide services to the youth. The overall objective of this paper is to unravel the emerging innovative social work techniques applied by youth empowerment organizations that seek to achieve social transformation among the youth. This study is grounded on diffusion of innovation model and linear models of innovation. This study reviewed different articles related to social work techniques, social work methods, social work intervention books, youth empowerment programs, social innovations, and existing local and international literature using different material from related fields to get rich information. The reviewed literature revealed that there were new social work techniques that have emerged to address the needs of the contemporary and dynamic urban youth population. These innovations have neither been documented nor shared with other organizations and social work practitioners. Social workers also face challenges in developing new techniques and these contributes to poor outcomes with the concurrent diversity of the social problems. This study recommends documentation of emerging social work interventions in youth empowerment and development programs, sharing of information and utilization on the new techniques and methodologies among social workers working with the youth. Social workers need to be trained on how to utilize social research to enhance their capacity in technique development, and organizing regular seminars and workshops where social workers can share and learn more about the new and emerging social work interventions.